2019
DOI: 10.1016/j.soilbio.2019.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on soil microbial nitrogen use efficiency are controlled by allocation of organic nitrogen to microbial growth and regulate gross N mineralization

Abstract: Microbial nitrogen use efficiency (NUE) is the efficiency by which microbes allocate organic N acquired to biomass formation relative to the N in excess of microbial demand released through N mineralization. Microbial NUE thus is critical to estimate the capacity of soil microbes to retain N in soils and thereby affects inorganic N availability to plants and ecosystem N losses. However, how soil temperature and soil moisture/O2 affect microbial NUE to date is not clear. Therefore, two independent incubation ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 70 publications
4
54
2
Order By: Relevance
“…Elevated temperature has been found to increase microbial growth and enzyme activities (Barcenas‐Moreno, Gomez‐Brandon, Rousk, & Baath, 2009). The increase of enzyme activities promotes turnover or depolymerization of soil organic C, N, and P, thereby increasing the substrate availability for microbial uptake (Zhang, Zheng, Noll, Hu, & Wanek, 2019). For example, we found that both microbial N immobilization rates (iNH4 and iNO3) increased significantly with temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated temperature has been found to increase microbial growth and enzyme activities (Barcenas‐Moreno, Gomez‐Brandon, Rousk, & Baath, 2009). The increase of enzyme activities promotes turnover or depolymerization of soil organic C, N, and P, thereby increasing the substrate availability for microbial uptake (Zhang, Zheng, Noll, Hu, & Wanek, 2019). For example, we found that both microbial N immobilization rates (iNH4 and iNO3) increased significantly with temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The intensive use of nitrogen (N) fertilizers in agro-ecosystems is driven by a growing demand of food for a global human population of more than 11 billion by 2100 (Gerland et al 2014;Gruber and Galloway 2008). However, nitrogen use efficiency (NUE) is rarely exceeding 50%, as majority of N fertilizers is lost to the environment through nitrate leaching, nitrous oxide (N2O) emission, and ammonia volatilization (Wang et al 2018a;Zhang et al 2019). Application of nitrification inhibitors (NIs) together with N-based fertilizers is a practical tool to reduce N losses and to promote plant NUE in order to increase crop yields in agricultural systems ( Dinnes et al 2002;Subbarao et al 2006;Di and Cameron 2012;Shi et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at low soil moisture microbial cell dehydration occurs which lowers the activity of nitrifying bacteria (Stark & Firestone 1995). Thus, the efficiency of soil processes are stimulated under higher soil moisture (Zhang et al 2019b). Finally, soil moisture can alter soil nitrification and denitrification where both processes can produce N 2 O (Bollmann & Conrad 1998).…”
Section: Discussionmentioning
confidence: 99%